Susceptibilidade de populações de Simulium (Chirostilbia) pertinax Kollar, 1832 (Culicomorpha, Simuliidae) ao temephos e a um formulado à base de Bacillus thuringiensis var. israelensis Susceptibility of population of Simulium (Chirostilbia) pertinax Kollar, 1832 (Culicomorpha, Simuliidae) to temephos and Bacillus thuringiensis var. israelensis formulation - Carlos Fernando S. de Andrade; Armando Castello Branco Jr (Universidade de São Paulo, 1991)
O uso de pequenas calhas de madeira no leito de riachos, manualmente colonizadas com borrachudos, é proposto para avaliações da eficiência de larvicidas 3 ou 4 horas após as aplicações. A susceptibilidade larval também foi avaliada pelo critério de TL50. Em três ensaios no litoral do Estado de São Paulo e Rio de Janeiro, populações de Simulium (C.) pertinax Kollar, 1832 mostraram-se resistentes ao temephos, mesmo em altas concentrações. Vectobac 12 AS, à base de Bacillus thuringiensis var. israelensis mostrou-se mais potente contra larvas dos últimos estádios e eficiente para controle em concentrações a partir de 7.200 UIP/1 (10 min.). O TL50para 3.744 UIP/1 (10 min.) foi de 70,9 minutos. The use of wooden troughs on stream beds, artificially colonized by blackfly larvae, is proposed for larvicide evaluations. Mortality was recorded 3 or 4 hours after treatment. Larval susceptibility was also evaluated utilizing the LT50 criterion. In there field assays Simulium (C.) pertinax populations from the litoral of S. Paulo and Rio de Janeiro States were shown to be resistant to temephos, even when subjected to high concentrations. Vectobac 12 AS, a Bacillus thuringiensis var. israelensis product, was shown to be more potent against late instar larvae and efficient in concentrations higher than 7,200 ITU/1 (10 min). The LT50 to 3,744 ITU/1 (10 min) was calculated as 70.9 min.